U-type versus J-type Tournaments as Alternative Solutions to the Unverifiability Problem - Matthias Kräkel (University of Bonn, Bonn Graduate School of Economics (BGSE), 2002)
This paper discusses the properties of stylized U.S. ("U-type") and Japanese tournaments ("J-type"), which can both solve the unverifiability problem of labor contracts. Under a zero-profit condition, both tournament types will yield first-best efforts if workers are homogenous and risk neutral. This result will no longer hold for J-type tournaments if the employer has all the bargaining power. However, if workers are rik averse or one worker has a lead a J-type tournament may dominate a U-type tournament.
Keywords: J31; J33; 330; Strategic Delegation; Mergers; Oligopoly; Contests